Pathological Laughing in a Patient with a Pontine Tumor - Nepal, Gopi; Gurung, Pritam; Jha, Anik; Khadka, Durga; Shrestha, Resha; Pant, Basant (Nepal Journal of Neuroscience, 2023)
An 18-year-old man presented with the complaints of occasional headache and limb weakness associated with slurring of speech and purposeless laughing. Magnetic resonance imaging showed a diffuse altered signal intensity area involving the pons with asymmetrical expansion. The patient underwent surgical resection. Histology was suggestive of a WHO grade IV glioblastoma. Pathological laughing in a patient with a pontine lesion is a very rare presentation. Evidence for a mechanism of action underpinning how pontine lesions can cause such behavioral changes through the disruption of a network of cerebro-ponto-cerebellar pathways is discussed.